Evolutionary adaptation of the sensitivity of connexin26 hemichannels to CO2. Issue 1848 (8th February 2017) - de Wolf, Elizabeth; Cook, Jonathan; Dale, Nicholas
Abstract : CO2 readily combines with H2 O to form and H + . Because an increase of only 100 nM in the concentration of H + (a decrease of 0.1 unit of pH) in blood can prove fatal, the regulated excretion of CO2 during breathing is an essential life-preserving process. In rodents and humans, this vital process is mediated in part via the direct sensing of CO2 via connexin26 (Cx26). CO2 binds to hemichannels of Cx26 causing them to open and allow release of the neurotransmitter ATP. If Cx26 were to be a universal and important CO2 sensor across all homeothermic animals, then a simple hypothesis would posit that it should exhibit evolutionary adaptation in animals with different homeostatic set points for the regulation of partial pressure of arterial CO2 (PaCO2 ). In humans and rats, PaCO2 is regulated around a set point of 40 mmHg. By contrast, birds are able to maintain cerebral blood flow and breathing at much lower levels of PaCO2 . Fossorial mammals, such as the mole rat, live exclusively underground in burrows that are both hypoxic and hypercapnic and can thrive under very hypercapnic conditions. We have therefore compared the CO2 sensitivity of Cx26 from human, chicken, rat and mole rat ( Heterocephalus glaber ). We find that both the affinity and cooperativity of CO2 binding to Cx26 have been subjected to evolutionary adaption in a manner consistent with the homeostatic requirements of these four species. This is analogous to the evolutionary adaptation of haemoglobin to the needs of O2 transport across the animal kingdom and supports the hypothesis that Cx26 is an important and universal CO2 sensor in homeotherms.